2018
DOI: 10.1039/c8ay00829a
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3D printing and modular microfluidics to integrate cell culture, injections and electrochemical analysis

Abstract: Fabrication of microchip-based devices using 3-D printing technology offers a unique platform to create separate modules that can be put together when desired for analysis. A 3-D printed module approach offers various advantages such as file sharing and the ability to easily replace, customize, and modify the individual modules. Here, we describe the use of a modular approach to electrochemically detect the ATP-mediated release of nitric oxide (NO) from endothelial cells. Nitric oxide plays a significant role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 61 publications
0
34
0
Order By: Relevance
“…Further, the sample injection module for cell analysis permitted the injection of 195 nL of sample loaded in a groove formed on a rotor structure. 38 These injectors with multi-port valves permit simple procedures for switching load/injection but also repetitive injection of different samples. However, sample load/injection systems with an external multi-port valve still have a dead-volume problem related to the parts connecting the valve and the microchip.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the sample injection module for cell analysis permitted the injection of 195 nL of sample loaded in a groove formed on a rotor structure. 38 These injectors with multi-port valves permit simple procedures for switching load/injection but also repetitive injection of different samples. However, sample load/injection systems with an external multi-port valve still have a dead-volume problem related to the parts connecting the valve and the microchip.…”
Section: Introductionmentioning
confidence: 99%
“…Current dynamic endothelial models applied the cells on a 2D flat surface-either a wall of a microchannel, the bottom of a reservoir, or a sealed porous membrane. However, some recent studies have shown that the biophysical cues of an ECM can affect cellular activities 13,[29][30][31] . Therefore, we hypothesized that the aligned fibrous topography (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Silk fibroin is a protein derived from raw silk, which has been widely used for biomedical applications due to its superior properties, including low immunogenicity, similarity to native ECMs, and ease of production [11,23]. Previous works showed that electrospun fibers from silk fibroin with submicron diameters are suitable substrates for 3D cell cul-tures [11,24]. Therefore, as shown in Figure 1A, we applied silk fibroin fibers with an average diameter of 0.8 ± 0.2 µm (mean of 200 fibers from 5 samples ± standard deviation) as the ECM for hepatocytes, with the control being a flat 2D substrate.…”
Section: The Fibrous Ecm and Basic Characterizations Of The Cellsmentioning
confidence: 99%